Physician Payment Mechanisms, Hospital Length of Stay and Risk of Readmission: Evidence from a Natural Experiment - Damien Échevin; Bernard Fortin (Institute for the Study of Labor (IZA), 2013)
We provide an analysis of the effect of physician payment methods on their hospital patients' length of stay and risk of readmission. To do so, we exploit a major reform implemented in Quebec (Canada) in 1999. The Quebec Government introduced an optional mixed compensation (MC) scheme for specialist physicians working in hospital. This scheme combines a fixed per diem with a reduced fee for services provided, as an alternative to the traditional fee-for- service system. We develop a model of a physician's decision to choose the MC scheme. We show that a physician who adopts this system will have incentives to increase his time per clinical service provided. We demonstrate that as long as this effect does not improve his patients' health by more than a critical level, they will stay more days in hospital over the period. At the empirical level, we estimate a model of transition between spells in and out of hospital analog to a difference-in-differences approach. We find that the hospital length of stay of patients treated in departments that opted for the MC system increased on average by 5.3% (0.35 days). However, the risk of readmission to the same department with the same diagnosis does not appear to be overall affected by the reform.
Keywords: J33; I10; I12; I18; C41; 330; physician payment mechanisms; mixed compensation; hospital length of stay; risk of re-hospitalisation; duration model; natural experiment